(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The purpose of this study was to determine how technology integration affects student learning. Classrooms are getting more and more technology, and the rapidly evolving nature of technology demands that it be integrated into the curriculum. Technology has the potential to improve student learning, but it can also have a negative impact on learning. While technology makes learning more convenient and enhances many learning opportunities, it can also be an overused tool that can have a negative impact on students’ ability to develop their fine motor skills and problem-solving skills. While integrating technology into the classroom has proven beneficial, it also has several disadvantages.Technology has helped student willingness and engagement and allows for the enhancements of learning. Reducing the obstacles that keep many children and schools from achieving greatness is something that teachers and students should take advantage of. Therefore, it is past time for every nation to put in place a future education system that is more technologically sophisticated.